Penerapan Tanggung Jawab Hukum Peternak Berbasis Ekonomi Sirkular dalam Pengelolaan Limbah Peternakan Kambing Etawa di Nusantara Farm - Mohammad Iqbalya; Nur Qoilun (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This study aims to analyze the implementation of legal responsibility by goat farmers in managing waste from Etawa goat farming based on a circular economy model at Nusantara Farm, Sidoarjo. The study employs both normative juridical and empirical juridical approaches, with data collection techniques including literature review, interviews, and field observations.The results indicate that waste management is carried out through direct utilization, such as using livestock manure as organic fertilizer, selling waste, and distributing it to the surrounding community. These practices demonstrate that waste is not disposed of carelessly but rather reused, thereby creating economic and functional value.From a legal perspective, this condition reflects the fulfillment of the farmers' responsibilities in accordance with applicable laws and regulations, particularly in efforts to prevent environmental pollution. Furthermore, these waste management practices partially embody the principles of the circular economy, especially in terms of reuse.However, the current waste management practices remain conventional and are not yet optimally integrated. Therefore, there is a need to develop a waste management model based on an integrated closed-loop system to enhance the economic value of waste while ensuring more effective environmental sustainability.